Rehabilitating Judas Iscariot in French literature - Hale, Frederick (Verbum et ecclesia, 2006)
During the nineteenth and twentieth centuries, numerous French literary artists, like their counterparts in several other countries, attempted to probe the personality and motives of Iscariot. Among the most prominent were Ernest Renan, François Mauriac, Paul Raynal, and Marcel Pagnol. They evinced noteworthy literary imagination but failed to answer adequately the questions they had posed in their efforts to rehabilitate their long-despised subject. Invariably, such factors as the sparsity of information about Judas in the gospels and inadequate authorial research militated against the success of their experiments. Moreover, the varying portrayals of Judas and the multiplicity of incompatible theories which were advanced to explain his underlying motive underscores the extreme difficulty of discovering what kind of man Judas was and what prompted him to betray Jesus.